Original Research: Porcine model for observing changes due to ischemia/reperfusion injury secondary to intra-abdominal endovascular balloon occlusion. Issue 16 (October 2016) - Chao, Chia-Sheng; Tsai, Chien-Sung; Wang, Yao-Horng; Liu, Yuan-Hao; Chen, Jian-Ming; Chang, Yee-Phoung; Chin, Hsien-Kuo; Chien, Shang-Tao; Lee, Tai-Ming; Yang, Shyh-Chyun
Compared with conventional aortic cross-clamping, endovascular balloon occlusion (EBO) is a valuable strategy in unstable ruptured abdominal aorta aneurysm patients; however, it is unclear how long the balloon may remain safely inflated. Using a porcine model, we evaluated the influence of different EBO time periods on intra-abdominal pressure (IAP) and the association between various pathophysiologic indicators and reperfusion time. Twelve healthy three-month-old domestic piglets were subjected to ischemia/reperfusion injury using EBO within the abdominal aorta. Animals were grouped as A, B, and C based on 30, 60, or 120 min of ischemic time, respectively. Changes in IAP, hemodynamic data, respiratory and renal function, and histology after reperfusion were compared with baseline measurements. All pigs gradually developed intra-abdominal hypertension after ischemia/reperfusion injury. IAP increased significantly after 4 h of reperfusion in all three groups (all P < 0.001) with maximal IAP reaching > 22 mmHg in 10 pigs. However, no significant intergroup differences were found. Cardiac output remained stable, but mixed venous oxygen saturation decreased significantly at 4 h after reperfusion (P < 0.05). The pH decreased significantly at 10 min in all three groups (all P < 0.001). Histological changes in the small intestine, lung, and kidney occurred secondary to aortic ischemia; however, no significant differences were noted between groups (P > 0.05). EBO within the abdominal aorta induced ischemia/reperfusion injury which led to intra-abdominal hypertension, pathological changes within multiple organs, and decreased mixed venous oxygen saturation after only 30 min of abdominal aortic ischemia.